Prognostic Significance of the Systemic Immune-Inflammation Index in Patients With Cholangiocarcinoma: A Meta-Analysis - Liu, Xue-chun; Jiang, Yue-ping; Sun, Xue-guo; Zhao, Jian-jian; Zhang, Ling-yun; Jing, Xue (Frontiers in Oncology, 2022)
Background: The systemic immune-inflammation index (SII) is a significant prognostic factor for neoplastic diseases. However, the prognostic value of SII in patients with cholangiocarcinoma (CCA) remains unclear. This meta-analysis aimed to investigate the prognostic value of preoperative SII in patients with CCA. Method: We systematically searched for relevant studies in PubMed, Scopus, EMBASE, Web of Science, PROSPERO, and Cochrane Library databases up to March 22, 2022. Hazard ratios (HRs) and 95% confidence intervals (CIs) were used to estimate the association between SII and survival outcomes, including overall survival (OS) and recurrence-free survival. Results: Five studies with 1402 patients were included in this meta-analysis to determine the prognostic value of preoperative SII. The results showed that a higher SII was associated with poor OS in patients with CCA who underwent invasive surgery (HR=1.916; 95% CI, 1.566–2.343; Z=6.329; P<0.001). The results were reliable in the subgroup analysis according to country, age, sample size, SII cutoff values, and treatment methods. Conclusions: A high preoperative SII appears to be an effective and practical method for monitoring survival in patients with CCA. Systematic Review Registration: International Platform of Registered Systematic Review and Meta-Analysis Protocols (INPLASY), identifier INPLASY202240015.